PROBLEMS OF SETTING STANDARDS FOR INSTITUTIONAL BASIS OF CITY MANAGEMENT WITH DISTRICT DIVISION - Mamonova , Valentyna (Theory and Practice of Public Administration, 2020)
There are two types of setting up the local government in the cities with district division: 1) formation of the district councils in the city, 2) non-formation of district councils in the city. Generalized the practice of local government formation of Ukrainian cities with district division. Emphasized that fluctuations between different approaches within a city occur quite often, in particular – decisions to disband the district councils in the city are being made, then they are being formed again, and eventually being eliminated. At the same time, district administrations are being formed, headed by the executive bodies of the city council. However, district administrations in the cities do not have their own district budget, they cannot manage municipal property objects. Defined the problematic field of the city district management and proposed to select the criteria for establishing a district in the city as an administrative-territorial unit. Justified the necessity to incorporate the concept of “territorial community of a city district” in the law on local government, as well as to determine the composition of local government bodies in the cities with district division but not formed district councils. Based on the global experience, it is advised to introduce in the cities the district division of the Institute of Local Ombudsmen as a service that represents the territorial communities in the city council, protects and defends the districts interests when making city council decisions. Recommended the measures to increase the public involvement in the city administration: 1) create a public council in the council of a city with a district division as a consultative and advisory body to represent the interests of the residents of the city districts during the decision-making process by the city council, as well as to exercise public control over the activity of the city ​​council in general and its executive bodies in particular; 2) form micro-district committees as bodies of local self-organization; 3) conduct consultative surveys on important issues of life and community development in the territorial communities of the city districts.